2016
DOI: 10.3897/compcytogen.v10i2.7939
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic behavior and H3K4m distribution in B chromosomes of Characidium gomesi (Characiformes, Crenuchidae)

Abstract: Characidium gomesi Travasso, 1956 specimens from the Pardo River have up to four heterochromatic supernumerary chromosomes, derived from the sex chromosomes. To access the meiotic behavior and distribution of an active chromatin marker, males and females of Characidium gomesi with two or three B chromosomes were analyzed. Mitotic chromosomes were characterized using C-banding and FISH with B chromosome probes. Meiocytes were subjected to immunofluorescence-FISH assay using anti-SYCP3, anti-H3K4m, and B chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Cases where B chromosomes pair with each other to form bivalents, trivalents, and multivalents have been reported in literature (e.g. Pauls and Bertollo, 1983 ; Dias et al, 1998 ; Basheva et al, 2010 ; Serrano et al., 2016 ). This element frequently forms a univalent in cells with only one B chromosome, resulting in irregular meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Cases where B chromosomes pair with each other to form bivalents, trivalents, and multivalents have been reported in literature (e.g. Pauls and Bertollo, 1983 ; Dias et al, 1998 ; Basheva et al, 2010 ; Serrano et al., 2016 ). This element frequently forms a univalent in cells with only one B chromosome, resulting in irregular meiosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among genomes of fish species bearing B chromosomes, the genus Characidium Reinhardt, 1867 exhibits interesting cytogenetic features; the B chromosomes probably originated independently in the different species of this group, whereas the heteromorphic ZZ/ZW sex chromosomes seem to have originated once in the genus. Therefore, the B chromosomes of Characidium oiticicai Travassos, 1967 originated interspecifically, whereas in Characidium gomesi Travassos, 1956 and Characidium pterostictum Gomes, 1947, these elements have an intraspecific origin from the sex chromosomes ( Pansonato-Alves et al 2014 , Serrano et al 2016 ). In the present study, a novel occurrence of B chromosomes is described for Characidium alipioi , a species in which these elements were not found until now.…”
Section: Introductionmentioning
confidence: 99%
“…aff. C. vidali displayed similar repetitive DNA sequences among B and sex chromosomes ( Pansonato-Alves et al 2014 , Pazian et al 2014 , Scacchetti et al 2015a , Serrano et al 2016 ), while Characidium oiticicai Travassos, 1967 and C. alipioi did not show such shared sequences ( Pansonato-Alves et al 2014 , Serrano et al 2017 , respectively). Despite their molecular homology, it was demonstrated that B and W chromosomes do not form multivalent pairings during meiosis in male and female C. gomesi individuals.…”
Section: Supernumerary and Sex Chromosomes In Characidiummentioning
confidence: 98%
“…Meiotic analyses revealed the bivalent pairing of the ZW chromosomes, as well as the bivalent plus one univalent formation in specimens carrying three B chromosomes ( Serrano et al 2016 ). Chromosome pairing does not always indicate complete homology between chromosomes ( Ramsey and Schemske 2002 ).…”
Section: Supernumerary and Sex Chromosomes In Characidiummentioning
confidence: 99%
See 1 more Smart Citation